Indian Folk Arts and Crafts
India\\\'s rich heritage is preserved in its folk arts and crafts. Today there is a tremendous interest in the rich heritage of Indian folk tradition. Immense in its variety and range, this tradition reflects the amazing diversity of the people who have created it. This book, concise yet comprehensive, and richly illustrated, tells the story of how the arts and crafts of an ancient and imaginative people can be related to their day-to-day living, their legends, myths and festivals. - See more at: http://www.printsasia.com/book/indian-folk-arts-and-crafts-himman-dhamija-jasleen-dhamija-8123722060-9788123722061#sthash.JgHVuyx8.dpuf